Disparitas Perlindungan Pekerja Migran di Tingkat Daerah: Analisis Hukum Administrasi atas Regulasi di Kuningan dan Indramayu - Iman Jalaludin Rifa’i; Mima Delita Anggraeni (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This study originates from a fundamental problem of regulatory disparity in the protection of Indonesian Migrant Workers (PMI) at the regional level, which creates legal uncertainty and unequal protection across local jurisdictions. The case study focuses on Indramayu and Kuningan Regencies, which demonstrate significant differences in the exercise of regional government’s attributive authority. Indramayu has implemented this authority through Regional Regulation No. 3 of 2021 on the Protection of Indonesian Migrant Workers, while Kuningan has not yet established a similar regulation. The absence of a regional regulation in Kuningan has resulted in a legal vacuum, weak administrative protection, and potential violations of the principles of legality and equality before the law. Using a normative juridical approach with a comparative analysis of local regulatory substance and the concept of attributive authority in administrative law, this study reveals that such regulatory disparity reflects an administrative failure to fulfill the constitutional obligation of local governments to protect their citizens, particularly vulnerable groups. Therefore, harmonizing regional regulations is an urgent corrective measure to ensure equal, lawful, and accountable legal protection for migrant workers across all regions.